Convergence to equilibrium attractor in models of dynamic confl ict systems with attractive interaction - Satur, O.R. (Reports of the National Academy of Sciences of Ukraine, 2023)
This study focuses on the construction of a model for dynamic conflict systems with attractive interaction. The behavior of trajectories in this system is influenced by a set of positive parameters. The existence of equilibrium states is proven, and their properties are examined. An explicit form of equilibrium states is established, and the issue of stability is investigated.